Young Children See a Single Action and Infer a Social Norm - Schmidt, Marco F. H.; Butler, Lucas P.; Heinz, Julia; Tomasello, Michael (Psychological Science, 2016)
Human social life depends heavily on social norms that prescribe and proscribe specific actions. Typically, young children learn social norms from adult instruction. In the work reported here, we showed that this is not the whole story: Three-year-old children are promiscuous normativists. In other words, they spontaneously inferred the presence of social norms even when an adult had done nothing to indicate such a norm in either language or behavior. And children of this age even went so far as to enforce these self-inferred norms when third parties “broke” them. These results suggest that children do not just passively acquire social norms from adult behavior and instruction; rather, they have a natural and proactive tendency to go from “is” to “ought.” That is, children go from observed actions to prescribed actions and do not perceive them simply as guidelines for their own behavior but rather as objective normative rules applying to everyone equally.